2017
DOI: 10.1038/s41598-017-01514-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1.5 GPa-strength with 50%-ductility by transformation-induced plasticity of non-recrystallized austenite in duplex steels

Abstract: Needs for steel designs of ultra-high strength and excellent ductility have been an important issue in worldwide automotive industries to achieve energy conservation, improvement of safety, and crashworthiness qualities. Because of various drawbacks in existing 1.5-GPa-grade steels, new development of formable cold-rolled ultra-high-strength steels is essentially needed. Here we show a plausible method to achieve ultra-high strengths of 1.0~1.5 GPa together with excellent ductility above 50% by actively utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 49 publications
2
24
0
1
Order By: Relevance
“…In the same context for V-alloyed MMn steel, Hu et al [38] reported a small increment in yield strength due to grain refinement, however, they emphasized the role of VC precipitates and dislocation hardening in increasing the yield strength. The observed increase in yield strength due to V alloying is in agreement with several studies [39][40][41][42] that reported solely the pronounced effect of V precipitates; however, the current study emphasizes additional effects, such as grain-boundary, solid-solution, and dislocation strengthening. Furthermore, the formation of precipitates is considered to be responsible for the suppression of the complete dislocation annihilation during annealing and hence increasing the yield strength via the dislocation hardening effect.…”
Section: Interplay Among Different Strengthening Effects Induced By Vsupporting
confidence: 92%
“…In the same context for V-alloyed MMn steel, Hu et al [38] reported a small increment in yield strength due to grain refinement, however, they emphasized the role of VC precipitates and dislocation hardening in increasing the yield strength. The observed increase in yield strength due to V alloying is in agreement with several studies [39][40][41][42] that reported solely the pronounced effect of V precipitates; however, the current study emphasizes additional effects, such as grain-boundary, solid-solution, and dislocation strengthening. Furthermore, the formation of precipitates is considered to be responsible for the suppression of the complete dislocation annihilation during annealing and hence increasing the yield strength via the dislocation hardening effect.…”
Section: Interplay Among Different Strengthening Effects Induced By Vsupporting
confidence: 92%
“…In Fig. 7 we summarize some recently designed HEAs that emphasize the TRIP effects 33,34,69,[74][75][76][77][78][79][80][81][82][83] ; some of these have already been included in Fig. 3, e.g., ref.…”
mentioning
confidence: 99%
“…Moreover, for samples aged at an elevated temperature, e.g., homogenization at 1200 K, LCO can develop to various degrees, from short-to-medium range all the way to ordered domains on nanometer scale 89,93 . The dislocation lines become wavier due to such complex spatial : [74] : [75] : [76] : [77] : [78] : [79] : [80] : [81] : [82] : [83] Fig . 7 Yield strength versus uniform tensile strain observed in recently reported multi-principal-element steels.…”
mentioning
confidence: 99%
“…Even though stacking faults (SF) are stored in large numbers due to the well-known low SF energy (SFE) of these FCC HEAs/MEAs ( 1 , 2 , 8 , 12 ), twinning became difficult in UFG grains, and, at room temperature, strain hardening remained inadequate to sustain uniform elongation after the MEA yields at >1 GPa ( 3 ). In general, plasticity-enhancing mechanisms in low-SFE alloys such as phase transformation [transformation-induced plasticity (TRIP)] ( 10 , 30 33 ) and twinning [twinning-induced plasticity (TWIP)] ( 1 , 2 , 34 41 ) all lose their potency in UFG and NG structures ( 34 , 35 , 42 , 43 ).…”
mentioning
confidence: 99%